PENGARUH STRUKTUR AKTIVA, UKURAN PERUSAHAAN DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2015 - Hayati, Raja Yunelshe Dwi; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to examine partially and simultaneously the effect of asset structure, firm size and sales growth on the capital structure. Where the independent variables in this study are the Structure of Assets, Company Size and Sales Growth.While the dependent variable is Capital Structure. The sample used is secondary data derived from the financial statements of food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2011 to 2015. This study uses secondary data from the company's financial statements. Samples and sampling using purposive sampling technique. Data analysis using simple and multiple linear regression analysis, t test, F test, and determination coefficient test with SPSS 20. The results of this study indicate that the asset structure variables partially (t test) affect the capital structure, the size of the company partially (t test) does not affect the capital structure of the company, while sales growth negatively affects the capital structure of listed food and beverage companies on the Indonesia Stock Exchange. The simultaneous test results (F) show the influence of asset structure variables, company size and sales growth on the capital structure of food and beverage companies listed on the Indonesia Stock Exchange.Keywords: asset structure, company size, sales growth and capital structure